2018
DOI: 10.1088/1361-6439/aac781
|View full text |Cite
|
Sign up to set email alerts
|

Electrode configuration and electrical dissipation of mechanical energy in quartz crystal resonators

Abstract: Mechanical resonators made with monolithic piezoelectric quartz crystals are promising for studying new physical phenomena. High mechanical quality factors (Q) exhibited by the mm-sized quartz resonators make them ideal for studying weak couplings or long timescales in the quantum regime. However, energy losses through mechanical supports pose a serious limiting factor for obtaining high quality factors. Here we investigate how the Q of quartz resonators at deep cryogenic temperatures can be limited by several… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Comparison with other HBAR and BAW resonators. Apart from the GaN/NbN/ SiC epi-HBAR data in this work, our study includes data reported in the literature from solid BAW overtone resonators fabricated from single-crystal bulk quartz, LiNbO 3 , and Si 6,7,17,24,25,42,[60][61][62] , as well as sputter-deposited HBARs on diamond 13,16,20,26,30 , fused silica 14 , quartz 14 , sapphire 5,14,15,21,27,28,63 , silicon 14,15,26,29 , and SiC 16,18,19,26 substrates. The sputter-deposited HBARs use polycrystalline piezoelectric AlN and ZnO thin films deposited on Al, Pt, Mo, and p + doped Si BE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with other HBAR and BAW resonators. Apart from the GaN/NbN/ SiC epi-HBAR data in this work, our study includes data reported in the literature from solid BAW overtone resonators fabricated from single-crystal bulk quartz, LiNbO 3 , and Si 6,7,17,24,25,42,[60][61][62] , as well as sputter-deposited HBARs on diamond 13,16,20,26,30 , fused silica 14 , quartz 14 , sapphire 5,14,15,21,27,28,63 , silicon 14,15,26,29 , and SiC 16,18,19,26 substrates. The sputter-deposited HBARs use polycrystalline piezoelectric AlN and ZnO thin films deposited on Al, Pt, Mo, and p + doped Si BE.…”
Section: Methodsmentioning
confidence: 99%
“…To systematically reduce net loss in the phonon cavity, it is necessary to reduce (if not eliminate) defect-based and interface-based phonon scattering. Many QAD experiments use bulk single-crystal overtone BAW resonators: massive macroscale devices with no internal interfaces and very low defect density 6,7,17,24,25 . However, such devices often require optomechanical actuation and are difficult to integrate into a compact system.…”
mentioning
confidence: 99%
“…The purpose of this study is to provide an overview of various ways of detection of physical quantities using oscillators with a piezoelectric crystal (as an oscillating element) and reactance connected in series or in parallel. The latter influences the crystal's electric substitute model and consequently its performance characteristics (the oscillating frequency near the resonance) [6][7][8]. The advantage of this method is great enhancement of sensor sensitivity, excellent temperature compensation, as well as compensation of capacitance among the crystal's electrodes and other parasitic impedances.…”
Section: Introductionmentioning
confidence: 99%